Seroprevalence of Cytomegolovirus Infection among Aborted Women in Thi-Qar Governorate - H. Al-Khafaji, Ahmad; I. Al-Zubaidi, Kawakib (University of Thi-Qar Journal of Science, 2010)
Venous blood had been collected from sexity women with habitual abortion from Thi-Qar Governorate cities to study and evaluate the prevalence of Cytomegalovirus infection and from twenty healthy looking women as control. The test performed using ELISA method to detect the IgM and IgG antibodies in patients and control sample by commercial kit. The result showed that 60 of 60 women (100%) had antibodies against CMV, 9 (15%) with IgM antibodies, 21 (35%) with IgG antibodies and 30 (50%) with both IgM and IgG antibodies. Other women (controls) they were negative for CMV infection.